Farm modelling for interactive multidisciplinary planning of small grain production systems in South Africa - Hoffmann, Willem Hendrik (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Agric) (Agricultural Economics)--University of Stellenbosch, 2010.